Book Review - Private Label Strategy: How to Meet the Store Brand Challenge - Pangriya, Ruchita (Indian Journal of Marketing, 2015)
The present book review analyzed Nirmalya Kumar and Jan - Benedict E. M. Steenkamp 's book - Private Label Strategy: How to Meet the Store Brand Challenge. This book brings together two areas - new strategy of retailers for private labels and strategy of brand manufacturers for private labels. Retailers in the present times are more powerful and globalized, and are focusing on their own brands to gain increased profits. Old myths about private labels have now vanished. Consumers' attitude towards private labels is remarkably positive, and it is a challenge for brand manufacturers to think again in a new frame. The main competitive advantage of manufacturer brands is the universal availability and innovation, and now, both are in trouble. A different approach is now essential if brand manufacturers want to stay in the game.